SHEAR BEHAVIOR OF FIBER REINFORCED CONCRETE COLUMN WITH HIGH STRENGTH REINFORCING BARS DUE TO AXIAL AND CYCLIC LATERAL LOAD - Julian, Jeremi
High strength reinforcing bars with yield strength of 500 MPa is commercially produced and used in construction structure in Indonesia. The use of high strength reinforcing bars is advantageous from both structural and architectural aspect. However, the use of such reinforcing bars to resist shear foce shear stress reinforcing bars is capped at 420 MPa, in order to control crack width and ensure the yield of shear reinforcing bars prior to longitudinal. The addition of fiber into concrete matrix can enhance the crack width, shear capacity, and ductility of concrete material. This experiment intented to know more about relation between the addition of fiber into concrete matrix to shear behavior, stress behavior of stirrups, and the enhancement of shear strength in concrete column element reinforced with high strength bars (520 MPa), both for shear and longitudinal used in this paper. A total of 4 specimens were tested in this experiment, loaded with axial and cyclic lateral load. The dimension of each specimen is rectangular 300x250 mm, with column clear height of 900 mm. Shear failure is expected to these specimens, due to the low amount of shear reinforcement provided in each specimen. The distance of stirrups is varies, either 125 mm (taken as d/2) or 185 mm. The result of experiment shows the yield of stirrups in all specimens prior to peak shear force. The use of 1% polypropylene fiber shows the significant increase of peak shear force, dissipated energy, and decrease crack width.